Plant Phenolics with Antiviral Activities against Human Corona Virus and Structure-Activity Relationships – A Review - Arimboor, Ranjith (Pharmacognosy Reviews)
The ability of human coronaviruses to infect respiratory tracts and transmit through respiratory droplets makes them highly contagious and potential to become pandemic. The current pandemic situation developed due to COVID-19 infection warrants the rapid development of effective and safe antivirals for disease management. Natural products are considered as a reliable and valuable source for rapid drug discovery. Phenolics, a major class of plant secondary metabolites, have been screened on a large scale for their antiviral efficacy to combat emergent mutants of coronavirus. Phenolics have a lower risk for the development of toxicity comparing to synthetic compounds as we are naturally adapted to most of the plant Phenolics as part of our vegetarian diet. The available literature has shown that Phenolics could interfere with the various key enzymes associated with virus-host cell interactions and thus alleviate the severity of the disease. The review of structure-activity relationships indicated the roles of hydrophobic aliphatic side chains, catechol groups, pyran ring, glycosylation, flexible linkages between aromatic rings, etc in modulating the interactions of Phenolics with human coronavirus proteins. The summary of the current literature available in this review might be useful for the selection of Phenolics with diverse structural properties and to design semi-synthetic products with better drug properties against coronaviruses.
Keywords: Coronavirus; SARS; MERS; PLpro; 3CLpro; RdRp; N-protein; Polyphenols